Direct Synthesis of Ag Nanoparticles Incorporated on a Mesoporous Hybrid Material as a Sensitive Sensor for the Simultaneous Determination of Dihydroxybenzenes Isomers - Canevari, Thiago C. [UNESP]; Raymundo-Pereira, Paulo A. [UNESP]; Landers, Richard; Machado, Sergio A. S. [UNESP] (Wiley-Blackwell, 2013)
This paper describes the synthesis, characterization, and applications of a mesoporous silica/ multiwalled carbon nanotube (SiO2/MWCNT) hybrid material, which was obtained by a sol-gel process and decorated with silver nanoparticles (AgNPs) ranging in size from 5 to 8 nm. The AgNPs were prepared directly on the surface of the SiO2/MWCNTs material by using N,N-dimethylformamide (DMF) as the reducing agent, and the resulting material was designated Ag/SiO2/MWCNT. The Ag/SiO2/MWCNT material was characterized by scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), high-resolution transmission electron microscopy (HR-TEM), and X-ray photoelectron spectroscopy (XPS). A glassy carbon electrode, modified with the Ag/SiO2/MWCNT material, was used in the development of a sensitive electrochemical sensor for the determination of hydroquinone and catechol in the presence of resorcinol by squarewave voltammetry. Well-defined and separate oxidation peaks were observed in phosphate buffer solution (PBS) at pH 7. The Ag/SiO2/MWCNT-modified electrode exhibited high sensitivity for the simultaneous determination of hydroquinone and catechol in the presence of resorcinol, and the limits of detection for hydroquinone and catechol are 0.0117 and 0.0121 M, respectively. No significant interference was seen for 2,6-dichloroindophenol, phenol, 4-nitrophenol, and nitrite ions in the detection of dihydroxybenzenes. Our study demonstrates that the resultant Ag/SiO2/MWCNT-modified electrode can be used for hydroquinone and catechol detection in the presence of resorcinol and other potentially interfering materials in river water samples.
Keywords: Nanoparticles; Hybrid materials; Sensors; Silver; Dihydroxybenzenes